Pengaruh Pengungkapan Media Terhadap Nilai Perusahaan Saat Pandemi Covid-19 Pada Perusahaan Retail dan Grosir yang Terdaftar di Bursa Efek Indonesia - Muhammad Hidayat; Abdullah Saggaf; Muhammad Ichsan Siregar; Ery Erman (Owner : Riset dan Jurnal Akuntansi, 2023)
The purpose of this study was to see the positive and negative effects of Media Disclosure on firm value in retail and wholesale companies in Indonesia. The media is very influential on the value of a company, where investors can find out the condition of the company not only through internal information, investors also get information from external parties through news in print and electronic media. The population of this study were 70 retail and wholesale companies listed on the Indonesian stock exchange. 21 companies became the research sample during 2019 and 2020 using purposive sampling. Methods of data analysis using multiple linear regression. The results of the study show that positive media disclosure has no significant effect, while negative media disclosure has a significant effect on firm value. If there is positive disclosure by the media about the company, the effect is very small on the value of the company. This is because investors' trust in positive disclosures is still questionable about its validity and investors believe that positive disclosures by the mass media need to be examined again. The results of the study show that management plays an important role in managing information in online media that is easily accessible to the public. Management's accuracy in responding to developing issues, especially negative company issues.